Propose a Wall Shear Stress Divergence to Estimate the Risks of Intracranial Aneurysm Rupture. (26th September 2013) - Zhang, Y.; Takao, H.; Murayama, Y.; Qian, Y.
Abstract : Although wall shear stress (WSS) has long been considered a critical indicator of intracranial aneurysm rupture, there is still no definite conclusion as to whether a high or a low WSS results in aneurysm rupture. The reason may be that the effect of WSS direction has not been fully considered. The objectives of this study are to investigate the magnitude of WSS (WSS ) and its divergence on the aneurysm surface and to test the significance of both in relation to the aneurysm rupture. Patient-specific computational fluid dynamics (CFD) was used to compute WSS and wall shear stress divergence (WSSD) on the aneurysm surface for nineteen patients. Our results revealed that if high WSS is stretching aneurysm luminal surface, and the stretching region is concentrated, the aneurysm is under a high risk of rupture. It seems that, by considering both direction and magnitude of WSS, WSSD may be a better indicator for the risk estimation of aneurysm rupture (154).